Educational Privatization and Inspection: An International Comparison Based on a Multilateral Political Context - Rodríguez Muñoz, María (Avances en Supervisión Educativa, 2026)
Education is changing. The 21st century is seeing a proliferation of privatization, neoliberalism, and the commercialization of education; however, little research has been done on the role of educational inspection or school supervision in these developments. The objective has been to analyze the impact of educational privatization on the education system in general, and on educational inspection in particular in Latin America and Spain, with the aim of investigating how neoliberalism and pro-market ideas have become involved in ways of educating using resources more typical of businesses than of education. The evolution of this issue in Argentina, Chile, and Spain is observed in order to see if education is a free-market commercial service. The methodology used is the comparative method, using documentary analysis as a data collection tool. The results suggest that the role of inspection in the Latin American countries analyzed is irrelevant. In Spain, public education is losing ground, and the challenges posed by neoliberalism make it difficult for the education inspectorate to efficiently fulfill its regulatory role of promoting equity and social justice.
Keywords: inspección educativa; supervisión educativa; políticas educativas; privatización; neoliberalismo; equidad; justicia social; sistema educativo.